(untitled) (Research, Society and Development, 2022)
Objective: the present study sought to investigate the contribution in some physicochemical parameters of the addition of cupuassu butter to the formulation of a glycerin-based soap. Proving the validity of cupuassu butter as a cosmetic additive would be of great importance to the local economy. Methodology: glycerin-based soaps were prepared, one group with butter, and the other without. Tests were then carried out in duplicate on water absorption, durability, cracking, saponification index, acidity index, foam volume, melting point and pH. Results: the addition of butter brought an improvement in the aspects of durability, foam volume, melting point and pH, while the parameters of acidity index and water absorption had a slight worsening, which did not compromise the quality of the soap. Conclusion: cupuassu butter appears to be a good option for a cosmetic additive, and further studies are needed to investigate its pharmacological properties in topical use.